Education and Implementation of Catfish Farming in Tarpaulin Ponds for Students of SMP Negeri 3 Manganitu as a Strategy for Contextual Learning and Enhancing Food Self-Sufficiency: Edukasi dan Implementasi Budidaya Ikan Lele di Kolam Terpal bagi Siswa SMP Negeri 3 Manganitu sebagai Strategi Pembelajaran Kontekstual dan Peningkatan Kemandirian Pangan - Numisye Iske Mose; Magdalin Ulaan; Edwin Oscar Langi (Mattawang: Jurnal Pengabdian Masyarakat, 2026)
The introduction of catfish as a source of animal protein is important for students, as catfish can contribute to fulfilling nutritional needs within the community. Early exposure to catfish aquaculture provides students with initial knowledge and understanding of fish farming, which can foster their interest in engaging in aquaculture activities. This community service activity was carried out in the hall of SMP Negeri 3 Manganitu and was attended by students and teachers of the school. The program implemented a participatory learning and action approach. This activity is essential for junior high school students because they are the next generation who need to be equipped with knowledge and skills that may support them in becoming future fish farmers or individuals who can promote catfish as an accessible source of animal protein, thereby reducing dependence on capture fisheries. The results of the activity show that all participating students have become familiar with catfish and tarpaulin ponds as freshwater fish and freshwater culture systems, which they had not previously encountered.